Macroprudential approach to regulation: Scope and issues - Shyamala Gopinath (Asian Development Bank Institute (ADBI), 2011)
This paper provides an overview of the Reserve Bank of India's approach to macroprudential regulation and systemic risk management, and reviews lessons drawn from the Indian experience. It emphasizes the need for harmonization of monetary policy and prudential objectives, which may not be possible if banking supervision is separated from central banks. It also notes that supervisors need to have the necessary independence and flexibility to act in a timely manner on the basis of available information. Macroprudential regulation is an inexact science with limitations and needs to be used in conjunction with other policies to be effective.
Keywords: E52; E58; G28; 330; Finanzmarktkrise; Kapitalmarktliberalisierung; Bankenaufsicht; Börsenaufsicht; Indien